An action research on instilling cooperation among chorale groups in the Most Holy Redeemer Parish Liturgical Music Ministry - Chan, Marie Christine P. (Animo Repository, 2015)
This action research aims to address the deteriorating cooperation of the different chorale groups within the Liturgical Music Ministry of the Most Holy Redeemer Parish (MHRP) at Barangay Masambong, Quezon City. The issue affects successful roll-out of the ministry's project. This study used the following methods: (1) a focus group discussion involving the Parish Priest, Worship Ministry Head and the representatives of the music ministry (2) focus group discussions casual interviews with the ministry elders and dissemination surveys to the ministry. The action research shows that diversity in tenure of service causes the feeling of intimidation and lack of interest among members in joining ministry activities. To resolve this issue, a monthly activity was agreed upon by the ministry elders decided, such as choir practice, so the members of each chorale group would be acquainted with each other. This intervention is just the beginning of a more in depth resolution to address the issue of cooperation in the ministry.